“Maybe We Shouldn’t Laugh So Loud”: The Hostility and Welcome Experienced by Foreign Nurses on Temporary Work Permits in Nova Scotia, Canada - Nourpanah, Shiva (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
My research explores the labour conditions experienced by foreign nurses employed in health care in the province of Nova Scotia, Canada, on temporary permits. I draw on ethnographic interviews to understand the nuanced ways in which foreign nurses feel welcomed in their local communities and workplaces, yet simultaneously remain subject to hostile racialized scrutiny. Nova Scotia is one of the least ethnically diverse provinces in Canada and one of the most economically impoverished. It faces a shortage of healthcare workers, exacerbated by the ongoing restructuring of the healthcare sector. These contextual factors contribute to the complicated push-pull matrix discussed by the temporary foreign nurses, who feel needed, but not wanted. This matrix cannot be dismissed as simply the racism and “backwardness” of local communities. Rather, it must be understood through a political economy focus on temporary foreign workers, restructured health care, and the normalization of a precarious labour landscape in which racialized foreign and local workers are pitted against each other.